Analisis Penggunaan Limbah Gypsum Sebagai Filler Terhadap Kuat Tekan Beton - Martua Sihombing, Sahat; Indriasari; Riyan Prasetyo (Jurnal Sipil Krisna, 2023)
Infrastructure development spurred innovation in the field of structural engineering, particularly in the field of construction materials technology. The development of concrete technology in trials of adding mixed ingredients continues to be carried out to obtain the desired strength and quality of concrete. The characteristics of concrete are greatly influenced by the ingredients contained in the mixture and how it is processed. The purpose of this study was to analyze the normal compressive strength of concrete and the compressive strength of concrete using gypsum waste as a filler with variations of 10% and 20% with curing ages observed at 28 days. The method used in this study is an experimental method or experiments in the Concrete Laboratory. Based on the results of the study, the normal compressive strength values of fc'18 (MPa) at ages 28 days were 18.08 MPa. In mixed variations of concrete with gypsum waste as a 10% filler, the compressive strength values at the ages of 28 days were 19.18 MPa. In mixed variations of concrete with 20% gypsum waste as filler, the compressive strength values at 28 days of age were 19.71 MPa. From the results of the research conducted, it can be concluded that the use of gypsum waste from the rest of the construction has an effect on increasing the compressive strength of concrete.